Library Information System Design at State Senior High School 5 Prabumulih - Dwie Oxtarini; Suhartini; Nurmayanti (Yayasan Kita Menulis, 2026)
Information systems using very sophisticated and modern computer technology will be very helpful and facilitate us in processing data that can save time, space and costs. Based on the existing problems, this study aims to design a web-based library information system at SMA Negeri 5 Prabumulih This system development method uses a research approach with SDLC or Software Development Life Cycle. While the model used in the design of this library information system is the agile model. The model provides a sequential or sequential software lifeflow approach starting from analysis, design, coding and testing. The programming language itself uses PHP with a codeigniter framework and for the database it uses MySQL/XAMPP. The results of this study show that the library information system at SMA Negeri 5 prabumulih is included in the feasible category after testing using black box testing category.